ISLAMIC ECONOMIC ANALYSIS OF THE ACEH SPECIAL AUTONOMY FUND MANAGEMENT - Fahmi, Chairul; Riyani, Syarifah (Kopertais Wilayah X Jawa Tengah, 2024)
Following the peace treaty, the Indonesian government enacted a new legislation that officially designates the Aceh Province as an area with special autonomy inside Indonesia. Subsequently, the government has been spending substantial financial resources to support this arrangement. However, Aceh continues to be the least affluent province in Sumatera and the fifth-most destitute in the entire country. The objective of this study is to investigate the underlying factors contributing to Aceh's persistently high poverty rate, as well as to analyse the strategies employed by the local government in managing the special fund in Aceh. The study employed a qualitative methodology, specifically adopting an empirical legal approach. The outcome signifies that the distribution of special autonomy funding for Aceh is exclusively applicable for a duration of 20 years, commencing from 2008 and concluding in 2027. For the initial 15-year period, Aceh was allocated 2% of the General Allocation Fund (DAU) from the State Budget (APBN) as Special Autonomy funding. During the period from 2023 to 2027, the quantity decreases to 1% in the subsequent phase. Regrettably, the administration of the special autonomy fund in Aceh lacks effectiveness in mitigating poverty and enhancing the well-being of the Acehnese populace. Consequently, the administration of Aceh's special autonomy funds deviates from the principles of finance and development in Islamic teachings. Additionally, the rulers have engaged in corrupt activities such as collusion and nepotism, which have impeded Aceh's progress in comparison to other provinces in Indonesia.